Shareholder Engagement in the Embedded Business Corporation: Investment Activism, Human Rights, and TWAIL Discourse - Dhir, Aaron (Business Ethics Quarterly, 2012)
The expansion of extractive corporations’ overseas business opera-tions has led to serious concerns regarding human rights–related impacts. As these apprehensions grow, we see a countervailing rise in calls for government interven-tion and in levels of socially conscious shareholder advocacy. I focus on the latter as manifested in recent use of the shareholder proposal mechanism found in corporate law. Shareholder proposals, while under-theorized, provide a valuable lens through which to consider the argument that economic behaviour is embedded within so-cial relations. In doing so, I situate my analysis within Third World Approaches to International Law (TWAIL) scholarship. Elsewhere, I have supported the use of corporate law tools in advancing the international human rights enterprise and argued that investment activism can be an essential component of this advancement. This paper represents a reflexive pause. Using the case study of a recent proposal submitted to Goldcorp Inc., I seek to problematize the shareholder proposal as a human rights advocacy tool and to examine it as a site of contestation.
Law
Keywords: Third World Approaches to International Law; corporate accountability; corporate law; law; shareholder rights